2023
DOI: 10.3390/electronics12030709
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Vilnius Chaos Oscillator-Based Digital Data Transmission Systems for IoT

Abstract: The current work is devoted to chaos oscillator employment in digital communication systems for IoT applications. The paper presents a comparative performance analysis of two different chaos data transmission systems: frequency-modulated chaos shift keying (FM-CSK) and quadrature chaos phase-shift keying (QCPSK), and a comparison to their non-chaotic counterparts: frequency-shift keying (FSK) and quadrature amplitude modulation (QAM). For both chaotic communication systems, the Vilnius oscillator and substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Chaos theory relates the chaotic dynamics of systems with initial conditions and unstable periodic motions [ 42 ]. It is applied in various applications such as biometric security [ 43 ], embedded systems [ 44 ], communications [ 45 ], lasers [ 46 ], pumped storage units [ 47 ], encryption systems [ 48 ], the Internet of Things [ 49 ], image processing [ 50 ], and image encryption [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chaos theory relates the chaotic dynamics of systems with initial conditions and unstable periodic motions [ 42 ]. It is applied in various applications such as biometric security [ 43 ], embedded systems [ 44 ], communications [ 45 ], lasers [ 46 ], pumped storage units [ 47 ], encryption systems [ 48 ], the Internet of Things [ 49 ], image processing [ 50 ], and image encryption [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Later, studies on the nonlinear dynamics of the oscillator and possible synchronization approaches have been provided [16,17]. However, the pronounced interest to the Vilnius oscillator has been shown since it has been adapted for practical IoT applications [18,19]. It has been demonstrated that the oscillator could be modified for utilization as a source of chaotic oscillations in secure data transmission systems.…”
Section: Introductionmentioning
confidence: 99%